Familial cortical dysplasia type IIA caused by a germline mutation in DEPDC5. (12th March 2015) - Scerri, Thomas; Riseley, Jessica R.; Gillies, Greta; Pope, Kate; Burgess, Rosemary; Mandelstam, Simone A.; Dibbens, Leanne; Chow, Chung W.; Maixner, Wirginia; Harvey, Anthony Simon; Jackson, Graeme D.; Amor, David J.; et al.
Abstract Whole‐exome sequencing of two brothers with drug‐resistant, early‐onset, focal epilepsy secondary to extensive type IIA focal cortical dysplasia identified a paternally inherited, nonsense variant of DEPDC5 (c.C1663T, p.Arg555*). This variant has previously been reported to cause familial focal epilepsy with variable foci in patients with normal brain imaging. Immunostaining of resected brain tissue from both brothers demonstrated mammalian target of rapamycin (mTOR) activation. This report shows the histopathological features of cortical dysplasia associated with a DEPDC5 mutation, confirms mTOR dysregulation in the malformed tissue and expands the spectrum of neurological manifestations of DEPDC5 mutations to include severe phenotypes with large areas of cortical malformation.